WIN55, 212-2 induces caspase-independent apoptosis on human glioblastoma cells by regulating HSP70, p53 and Cathepsin D. (June 2019) - Silva, Ana Gabriela; Lopes, Caio Fabio Baeta; Carvalho Júnior, Clóvis Gomes; Thomé, Ralph Gruppi; dos Santos, Hélio Batista; Reis, Rui; Ribeiro, Rosy Iara Maciel de Azambuja
Abstract: Despite the standard approaches to treat the highly aggressive and invasive glioblastoma (GBM), it remains incurable. In this sense, cannabinoids highlight as a promising tool, because this tumor overexpresses CB1 and/or CB2 receptors and being, therefore, can be susceptible to cannabinoids treatment. Thus, this work investigated the action of the cannabinoid agonist WIN55-212-2 on GBM cell lines and non-malignant cell lines, in vitro and in vivo . WIN was selectively cytotoxic to GBM cells. These presented blebbing and nuclear alterations in addition to cell shrinkage and chromatin condensation. WIN also significantly inhibited the migration of GAMG and U251 cells. Finally, the data also showed that the antitumor effects of WIN are exerted, at least to some extent, by the expression of p53 and increased cathepsin D in addition to the decreased expression of HSP70.This data can indicate caspase-independent cell death mechanism. In addition, WIN decreased tumoral perimeter as well as caused a reduction the blood vessels in this area, without causing lysis, hemorrhage or blood clotting. So, the findings herein presented reinforce the usefulness of cannabinoids as a candidate for further evaluation in treatment in glioblastoma treatment. Highlights: The synthetic cannabinoid, WIN-55, 212-2, shows strong and selective toxicity against glioblastoma cell lines. WIN-55, 212-2 reveals in vitro the inhibition of migration, invasion, and clonogenicity of GBM cell lines. WIN-55, 212-2 inhibited tumor growth in vivo and it can be safely administered parenterally.